1983
DOI: 10.1007/bf00237156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-hydroxydopamine on in vitro hippocampal corticosterone binding capacity in the male rat

Abstract: Adult male rats were injected with 6-hydroxydopamine, either into the lateral brain ventricle or directly into the dorsal hippocampus. They were adrenalectomized 5-7 days later, and following an additional 24 hours, the specific in vitro 3H-corticosterone binding capacity of dorsal hippocampal slices was determined by estimation of uptake of radioactivity by the nuclear fraction. Specific corticosterone binding was reduced by 40-50% in both experimental groups, as compared to vehicle-treated controls. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Previous studies using more selective de pleting agents indicate that both norepinephrine and serotonin depletions can decrease [3H]-corticosterone binding in the hip pocampus [10,11], However, serotonin depletions have also been reported to increase hippocampal [3H]-corticosterone binding [22]. In contrast, a single injection of the serotonergic neurotoxin, 3,4-methylenedioxymethamphetamine selectively decreased type II corticosteroid receptor levels in the striatum, but not in the hippocampus or frontal cortex [23].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies using more selective de pleting agents indicate that both norepinephrine and serotonin depletions can decrease [3H]-corticosterone binding in the hip pocampus [10,11], However, serotonin depletions have also been reported to increase hippocampal [3H]-corticosterone binding [22]. In contrast, a single injection of the serotonergic neurotoxin, 3,4-methylenedioxymethamphetamine selectively decreased type II corticosteroid receptor levels in the striatum, but not in the hippocampus or frontal cortex [23].…”
Section: Discussionmentioning
confidence: 95%
“…Neurotransmitters such as serotonin and norepi nephrine also have complex regulatory influences on brain cor ticosteroid receptors. This is based on studies using depleting agents such as 6-hydroxydopamine [10] and 5,7-dihydroxytryptamine [11] which have generally demonstrated that de creasing neuronal levels of serotonin and/or catecholamines decreases [3H]-corticosterone binding in the hippocampus. However, since biogenic amines are involved in adrenocortical regulation [ 12], the effects of biogenic amine depleting regi mens on corticosteroid receptor levels could be due to alter ations in circulating corticosterone levels rather than to a direct effect on receptor levels.…”
mentioning
confidence: 99%
“…GR and MR biosynthesis appears to be under control of central monoaminergic systems (Maccari et al, 1990(Maccari et al, , 1992Mitchell et al, 1990;Weidenfeld and Feldmann, 1991). In vivo studies with monoamine-depleting agents (eg reserpine) and neurotoxic substances that specifically destroy serotonergic, noradrenergic, and/or dopaminergic nerve terminals have provided evidence for a modulatory role of monoamines in brain corticosteroid receptor regulation (Lowy, 1990;Seckl et al, 1990;Siegel et al, 1983;Weidenfeld et al, 1983). After chronic fluoxetine treatment, in vivo microdialysis studies have shown that extracellular levels of serotonin are markedly elevated (Rutter et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, though chronic antidepressant administration may atte nuate corticosterone release to stress [31] (not tested in this study), some [28,29], though not all [23], reports sug gest that even major changes in glucocortioid levels have little effect per se on hippocampal corticosteroid receptor mRNA expression [28,29], Whether the action of antide pressants is mediated directly on hippocampal neurons [11,13,16], or indirectly, as shown by imipramine-induced alterations of GR immunoreactivity in mono amine-containing brain stem nuclei [32], is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In dissociated cultures of fetal hippocampal cells increased 5-HT concentrations lead to elevated glu cocorticoid but not mineralocorticoid binding sites [12], However, results in adult animals in vivo have been less clear-cut. Thus, neurotoxic lesions of the hippocampal serotoninergic innervation reduce corticosterone binding sites in nuclear extracts [13], but others have shown simi lar lesions increase cytosolic binding sites for corticoste rone [14], The hippocampal noradrenergic [15] (and/or dopaminergic) innervations may also play a role as cen tral 6-hydroxydopamine lesions reduce hippocampal nu clear corticosterone binding sites [16]. Reserpine, which depletes all monoamines, reduces both MR and GR in hippocampal cytosol [17], Antidepressant drugs, which inhibit 5-HT and/or noradrenaline reuptake and there fore potentiate monoamine actions, decrease cytosolic binding sites for corticosterone, but so do 5-HT receptor antagonists [14], Thus hippocampal monoaminergic in nervations may modulate corticosteroid receptor levels, although the receptor types involved (corticosterone binds to both GR and MR) and nature of the control are unclear.…”
mentioning
confidence: 99%